Is Job Stability in the United States Falling? - David A. Jaeger; Ann Huff Stevens (Institute for the Study of Labor (IZA), 1999)
Documenting trends in job stability over the past twenty-five years has become a controversial exercise. The two main sources of information on employer tenure, the Panel Study of Income Dynamics (PSID) and the Current Population Survey (CPS), have generally given different pictures of the degree of job stability in the U.S. economy. This paper examines whether the PSID and CPS yield systematically different results with respect to comparable measures of job stability. Both data sets show an increase in the fraction of male workers aged 30 and over with tenure less than ten years beginning in the late 1980s. There is little evidence in either data set of a trend in the share of employed individuals with one year or less of tenure. The two data sets provide nearly identical results for the 1980s and 90s while in the 1970s they give results that are somewhat less comparable. We argue that this is probably the result of changes in the CPS tenure question following the 1981 survey. The effects of this change and the choice of ending year and variable definition in PSID-based studies are the most likely explanations for the disparate findings in the literature.
Keywords: J63; J23; 330; Job stability; U.S economy; Arbeitsplatzsicherung; USA